OBSERVASI PERTUMBUHAN, HASIL RIMPANG DAN TINGKAT KETAHANAN SOMAKLON JAHE PUTIH BESAR TERHADAP PENYAKIT LAYU BAKTERI DI RUMAH KACA - sitti fatimah syahid; otih rostiana; tias arlianti (Pusat Penelitian dan Pengembangan Perkebunan, 2014)
Genetic variability in ginger is low, thus it is necessary to obtain new variants. The study was aimed to observe growth, yield and resistance level of ginger somaclones to Ralstonia solanacearum. The experiment was conducted under laboratory and a glass house condition at Indonesian Spice and Medicinal Crops Research Institute, Bogor from January to December 2010. The ginger somaclones used in this study were obtained from somaclonal induction using selection medium Acibenzolar-S-methyl and pathogenic bacteria filtrate at calli stage. The ginger somaclones were then planted at the green house. Four populations of ginger somaclones tested in this experiment were FA, FB, AC1 and FIPLA. All somaclones were inoculated with bacterial wilt disease suspension and then incubated for three months at the green house. The ginger somaclones then were planted in 60 cm x 60 cm polybag filled with 25 kg soil and 1 kg manure. The experiment used direct individual-observation method, without replications. The parameter observed were growth, yield and bacterial wilt disease infection, at 4 and 8 months after planting. The result showed that growth, rhizome yield and bacterial wilt disease infection varied among the somaclones population. Number of tiller, plant height, leaf number, length and width of leaf, stem diameter, rhizome weight and diameter were also varied among populations. Number of propagule of FA and FIPLA was higher than other populations. Visual morphology of somaclones tested were also varied. Based on bacterial wilt disease infection parameter, ginger somaclones population FA, FB, AC1 and FIPLA could be grouped from susceptible to tolerant.